2021
DOI: 10.3389/fphys.2021.744812
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Vagal Sensory Neurons via High Mobility Group Box-1 and Receptor for Advanced Glycation End Products: Implications for Respiratory Viral Infections

Abstract: Vagal sensory neurons contribute to the symptoms and pathogenesis of inflammatory pulmonary diseases through processes that involve changes to their morphological and functional characteristics. The alarmin high mobility group box-1 (HMGB1) is an early mediator of pulmonary inflammation and can have actions on neurons in a range of inflammatory settings. We hypothesized that HMGB1 can regulate the growth and function of vagal sensory neurons and we set out to investigate this and the mechanisms involved. Cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Animal studies also suggest that neural plasticity during pulmonary pathologies may relate to neuroinflammation within the vagus nerve or ganglia, characterized by increased inflammatory cell influx, upregulated inflammatory gene transcription and the release of inflammatory molecules from sensory neurons and resident or infiltrating immune cells 88 90 . The cause of this neuroinflammation is unclear, but likely relates to both peripheral vagal detection of tissue inflammation and adverse effects of inflammation-induced persistent firing of action potentials in sensory neurons 88 , 91 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Animal studies also suggest that neural plasticity during pulmonary pathologies may relate to neuroinflammation within the vagus nerve or ganglia, characterized by increased inflammatory cell influx, upregulated inflammatory gene transcription and the release of inflammatory molecules from sensory neurons and resident or infiltrating immune cells 88 90 . The cause of this neuroinflammation is unclear, but likely relates to both peripheral vagal detection of tissue inflammation and adverse effects of inflammation-induced persistent firing of action potentials in sensory neurons 88 , 91 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…We have previously shown that severe pulmonary IAV infections in mice are accompanied by a neuroinflammatory phenotype in the vagal sensory ganglia [19, 20]. To investigate whether peripheral sensory neuron activation in the lungs is involved in the development of vagal neuroinflammation, we compared the expression of inflammatory genes and inflammatory cell densities in the vagal sensory ganglia of IAV infected mice administered via inhalation from day 3 post IAV infection with either vehicle or QX-314 (Fig 2A).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that severe pulmonary IAV infections in mice are accompanied by a neuroinflammatory phenotype in the vagal sensory ganglia [19,20]…”
Section: Pharmacological Inhibition Of Pulmonary Sensory Neurons Impa...mentioning
confidence: 99%
“…One possibility is that the early processes leading to vagal sensory neuron damage establish a state of neuroinflammation within the vagal nerves and ganglia. This has been shown to occur following pathogen exposure in animal models of vagal hypersensitivity and is characterized by upregulated inflammatory cell influx into the nerve and ganglia, the activation of local glial cells, and the induction of proinflammatory genes [70][71][72]. Such a phenomenon might be expected to promote a state of sensory hypersensitivity in the period prior to sensory neuron destruction.…”
Section: Why Do Canvas Patients Have Chronic Cough?mentioning
confidence: 99%